Dataset on aerosol loading, size and statistics over Nzerekore - Emetere, M.E. (Data Brief, 2018)
Inadequate ground measuring equipment is becoming a global challenge. Most communities in West Africa rely only on satellite measurements. However, the volume of missing dataset in satellite measure over coastal communities is alarming. In this research, fifteen years primary (aerosol optical depth) dataset was obtained from the Multi-angle Imaging Spectro-Radiometer (MISR). The dataset presented in this research will serve as a research background for scientists working on the research site.